Exploring Entrepreneurial Intentions among Vocational High School Graduates: The Impact of Entrepreneurial Knowledge and Attitude - Maulida, Fita Hanan; Noviani, Leny; Sudarno, Sudarno (Indonesian Journal of Social Research (IJSR), 2024)
This research addresses the significant issue of unemployment among vocational school graduates in Indonesia and the low level of entrepreneurship among them. While previous studies have predominantly focused on the entrepreneurial intentions of high school and university student samples, there isthere needs to be more understanding of the entrepreneurial intentions of vocational school graduates. Bridging the gap, this study explores the determinants of entrepreneurial intentions among vocational school graduates, particularly examining the roles of entrepreneurial knowledge and attitude toward entrepreneurship. Additionally, this research explores attitude toward entrepreneurship as a mediating variable. The study employs a survey method with data from 305 vocational school graduates in Indonesia as participants. D ta analysis uses partial least squares structural equation modelling (PLS-SEM) with SmartPLS 4.0 software. The findings indicate that entrepreneurial Knowledge has a significant positive relationship with attitude toward entrepreneurship and entrepreneurial intention. Furthermore, this research finds that attitude toward entrepreneurship exhibits a complementary partial mediation effect between entrepreneurial Knowledge and entrepreneurial intention. The study also suggests that interest in entrepreneurship and professional experience can enhance the entrepreneurial intentions of vocational high school graduates. These insights offer valuable guidance for policymakers and educators in designing strategies to promote entrepreneurship among vocational school graduates, ultimately addressing unemployment challenges in Indonesia.